2015
DOI: 10.1186/s12886-015-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc morphology in unilateral branch retinal vein occlusion using spectral domain optical coherence tomography

Abstract: BackgroundThe aim of this study was to evaluate the association between optic nerve head (ONH) parameters and branch retinal vein occlusion (BRVO) using spectral domain optical coherence tomography (SD-OCT).MethodsBoth eyes of 40 patients with unilateral BRVO (mean age: 67.4 ± 11.4 years, male: female - 18:22) were enrolled in this study. Control group consisted of randomly selected single healthy eyes of 40 age and gender matched volunteers (mean age: 64.7 ± 15.4 years, male: female - 16:24). ONH parameters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Acute edematous changes and subsequent thinning of the RNFL could have caused this. Szigeti et al 20 reported that optic nerve head parameters, including the neuroretinal rim area, cup-to-disc area ratio, and RNFL thickness, of uninvolved fellow eyes and control eyes were not statistically different after controlling for axial length, age, and sex. These findings suggest that structural changes of the retinal layers could be within an undetectable range despite the presence of microvascular changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute edematous changes and subsequent thinning of the RNFL could have caused this. Szigeti et al 20 reported that optic nerve head parameters, including the neuroretinal rim area, cup-to-disc area ratio, and RNFL thickness, of uninvolved fellow eyes and control eyes were not statistically different after controlling for axial length, age, and sex. These findings suggest that structural changes of the retinal layers could be within an undetectable range despite the presence of microvascular changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies of RVO fellow eyes mainly aimed to reveal the cooccurrence of glaucoma and RVO in one patient because an increased risk of primary open angle glaucoma development in patients with RVO were reported by major epidemiologic studies. 4,[17][18][19][20][21] The vascular theory, which is the most widely recognized hypothesis regarding cooccurrence, 9,17 suggests that disturbance of the peripapillary blood circulation in both eyes of patients with RVO produces hypoxic damage of the optic nerve head, leading to glaucoma. The disturbance could be derived from certain systemic risk factors, such as hypertension, diabetes mellitus, and atherosclerosis, which are commonly associated with RVO.…”
Section: Discussionmentioning
confidence: 99%
“…Hayreh et al considered it as a separate type since its pathogenesis is quite similar to CRVO [10]. With the help of basic technology such as fundus photography, fundus fluorescein angiography (FFA), spectral domain optical coherence tomography (SD-OCT), visual field testing, and full-field electroretinogram (ff-ERG), BRVO and macular edema are usually easy to diagnose and classify [1114]. In addition, new technology such as OCT angiography (OCTA) can measure vascular density and the foveal avascular zone.…”
Section: Classificationmentioning
confidence: 99%
“…Similar results have been described by Ahn J et al in 2021 [ 12 ]. Some authors believe that retinal nerve fiber layer thinning should be considered the “natural course after branch retinal vein occlusions” [ 13 ], meanwhile others tried to underline that “optic disc swelling can cause difficulties in evaluating ONH parameters” [ 14 ]. Moreover, our study showed that no statistical differences between affected eyes with preexisting glaucoma and affected eyes without preexisting glaucoma have been found, which demonstrates that an associated glaucoma with a proper control of the intraocular pressure will not accelerate or have a direct contribution on the nerve fiber layer thinning throughout the years.…”
Section: Discussionmentioning
confidence: 99%